Outcomes of Laparoscopic TAPP Inguinal Hernia Repair without Mesh Fixation - Iqbal, Sajid (Lietuvos chirurgija, 2023)
Inguinal hernia repair is one of the commonest general surgical procedures performed worldwide. Laparoscopic repair is associated with faster recovery, less post operative pain and comparable rates of recurrence. Using the stapling devices increases post TAPP chronic groin pain. We conducted a prospective trial for laparoscopic TAPP inguinal hernia repair on 43 patients in which we did not fix the mesh. The primary purpose of this study was to examine the rate of recurrence and chronic groin pain in patients undergoing TAPP mesh hernia repair for inguinal hernia. We observed that our rates of recurrence and chronic groin pain are comparable to those described previously in the literature. We concluded that laparoscopic inguinal hernia repair by TAPP approach can be done with acceptable rates of recurrences and decreased rates of post operative chronic groin pain.